2010
DOI: 10.1038/nn.2536
|View full text |Cite
|
Sign up to set email alerts
|

Chordin-induced lineage plasticity of adult SVZ neuroblasts after demyelination

Abstract: The mechanisms that regulate the developmental potential of adult neural progenitor populations under physiological and pathological conditions remain poorly defined. Glutamic acid decarboxylase 65 (GAD65)- and Doublecortin (Dcx)-expressing cells constitute major progenitor populations in the adult mouse subventricular zone (SVZ). Under normal physiological conditions, SVZ-derived GAD65-positive and Dcx-positive cells expressed the transcription factor Pax6 and migrated along the rostral migratory stream to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
209
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(224 citation statements)
references
References 49 publications
13
209
0
1
Order By: Relevance
“…To elucidate the underlying mode of action, we investigated levels of gene expression of major BMP antagonists such as chordin, noggin and follistatin (Jablonska et al, 2010;Walsh et al, 2010). Consistent with our findings that upon p57kip2 suppression astrocytic markers were downregulated, and that these cells lost astrocytic morphological features, we detected a strong induction of chordin expression in FACS isolated cells (Fig.…”
Section: Bmp Antagonists Are Upregulated Upon P57kip2 Suppressionsupporting
confidence: 83%
See 1 more Smart Citation
“…To elucidate the underlying mode of action, we investigated levels of gene expression of major BMP antagonists such as chordin, noggin and follistatin (Jablonska et al, 2010;Walsh et al, 2010). Consistent with our findings that upon p57kip2 suppression astrocytic markers were downregulated, and that these cells lost astrocytic morphological features, we detected a strong induction of chordin expression in FACS isolated cells (Fig.…”
Section: Bmp Antagonists Are Upregulated Upon P57kip2 Suppressionsupporting
confidence: 83%
“…It is possible that, in the p57kip2-dependent glial fate regulation process, chordin and noggin act as cell-intrinsic safeguards in a BMP-enriched environment, as it was shown to occur upon transplantation into the spinal cord (Setoguchi et al, 2004;Hampton et al, 2007;Matsuura et al, 2008). In addition, the recent demonstration that chordin promotes oligodendrogenesis from adult NSCs in vitro and in vivo (Jablonska et al, 2010) suggests that a cell-autonomous induction of chordin actively contributes to the establishment of oligodendroglial features. However, because in this study chordin infusion induced Mash1 positivity, which we did not observe upon p57kip2 suppression, it remains to be shown whether similar molecular processes are NSCs transfected with control (H1) or p57kip2 suppression vectors (H1-kip2) were sorted (FACS).…”
Section: Underlying Molecular Mechanismsmentioning
confidence: 99%
“…Thus, our data are consistent with there being enhanced differentiation of resident OPCs in Noggin-infused mice. Jablonska et al (2010) found that infusion of Chordin, a BMP antagonist with slightly lower affinity for BMP4 than Noggin (Piccolo et al, 1996), induced the differentiation of DCX-expressing cells of the adult SVZ into oligodendrocytes in lysolecithin-demyelinated CC. Thus, the combined data suggest that both inhibitors of BMP signaling (i.e., Chordin and Noggin) can increase the production of oligodendrocytes in vivo in the context of demyelination and that infusion of these substances are likely to have composite effects within the SVZ and the demyelinated lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In adult the dentate gyrus, Xiong and colleagues showed that in the inner molecular layer, the spine density of newly generated dentate granule cells increases first and then deceases one month after tamoxifen administration [6], which is in contrast to a previous finding that the spine density in the outer molecular layer continues to increase within the same time window [15]. In the adult subventricular zone, Gallo and colleagues showed that DCX-expressing neuroblasts exhibit surprising lineage plasticity and can be redirected from neuronal to glial fates, generating new oligodendrocytes in the corpus callosum after demyelination [11].…”
mentioning
confidence: 78%
“…Intriguingly, DCX expressing neuroblasts in the subventricular zone, the largest germinal region in the adult brain which gives rise to newborn interneurons in the olfactory bulb, were not labeled after tamoxifen induction in these mice. We have independently generated multiple lines of BAC based DCX-CreER T2 mice [11]. Interestingly, only the DCX expressing newborn neurons in the adult subventricular zone are targeted in our mice, not in the adult dentate gyrus.…”
mentioning
confidence: 99%